Effect of the orientation of laser stripes on the abrasion resistance of biomimetic laser textured surfaces. (November 2018) - Su, Wei; Zhou, Ti; Zhang, Peng; Zhou, Hong; Li, Hui; Sui, Qi
Highlights: Samples were covered with different orientated bionic laser stripes. Worn topographies of different orientated laser stripes were explained. The effect of laser scanning rate on laser stripes were studied. Abstract: In order to improve the anti-wear performance of the semi-arc of trailer's brake shoes, we utilized biomimetic laser texturing to fabricate special striated textures which can play roles in dispatching stress as researched in our previous studies. The orientation of biomimetic stripes was proven to be an important factor to the abrasion resistance of textured surfaces, thus blank samples cut from a brake shoe were modified with 0°, 30°, 45°, 60° and 90° angular distributed laser stripes on their surfaces. All samples undergone 10 hours of dry sliding experiments. The wear result indicated: (i) The biomimetic surface covered with 45° angular distributed stripes has the lowest wear mass loss and the wear resistance of all biomimetic surfaces shown an ascend trend at first and a descend trend at last with the increase of angle between stripe and the wear direction. (ii) When the angle between stripe and the wear direction is 0° (Stripes are parallel to the wear direction), the wear extent was most serious, however, when the angle was changed into 90°, we could deduce that the wear particles could be hindered and accumulated debris and particles would continuously plow softer surface. Only when the angle change into 45° can abrasives be hindered and dispersed in an effective way.